2013
DOI: 10.1002/phy2.37
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1receptor signaling inhibits BK channels through a PKCα-dependent mechanism in mouse aortic smooth muscle

Abstract: Adenosine receptors (AR; A1, A2A, A2B, and A3) contract and relax smooth muscle through different signaling mechanisms. Deciphering these complex responses remains difficult because relationships between AR subtypes and various end-effectors (e.g., enzymes and ion channels) remain to be identified. A1AR stimulation is associated with the production of 20–hydroxyeicosatetraenoic acid (20–HETE) and activation of protein kinase C (PKC). 20–HETE and PKC can inhibit large conductance Ca2+/voltage-sensitive K+ (BK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In addition, CYP4A contributes to the development of angiotensin II‐dependent hypertension (McGiff and Laniado‐Schwartzman, ; Harder et al, ; Haller et al, ; McGiff et al, ; Muthalif et al, ; ; Zaman et al, ). PLC, 20‐HETE and ERK1/2 pathways are involved in the regulation of vascular tone by adenosine through the activation of A 1 receptors (Rogel et al, ; Jacobson and Gao, ; Ponnoth et al, ; Kunduri et al, ; Kunduri et al, ). Thus, we believe that acute angiotensin II stimulation may alter adenosine receptor‐dependent signalling, establishing an important role for adenosine in the regulation of vascular tone in MAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, CYP4A contributes to the development of angiotensin II‐dependent hypertension (McGiff and Laniado‐Schwartzman, ; Harder et al, ; Haller et al, ; McGiff et al, ; Muthalif et al, ; ; Zaman et al, ). PLC, 20‐HETE and ERK1/2 pathways are involved in the regulation of vascular tone by adenosine through the activation of A 1 receptors (Rogel et al, ; Jacobson and Gao, ; Ponnoth et al, ; Kunduri et al, ; Kunduri et al, ). Thus, we believe that acute angiotensin II stimulation may alter adenosine receptor‐dependent signalling, establishing an important role for adenosine in the regulation of vascular tone in MAs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in chronic angiotensin II and L-NAME hypertension mouse models, genetic deletion of A 1 receptors has been shown to attenuate arteriolar and BP responses (Gao et al, 2011;Lee et al, 2012). Previously, we demonstrated that CYP4A and ERK1/2 are involved in the A 1 receptordependent contractile response in mouse aorta (Ponnoth et al, 2012a;Kunduri et al, 2013b;Kunduri et al, 2013a). In agreement, our data revealed that enhanced vasoconstriction to NECA in MAs following angiotensin II stimulation was completely dependent on the A 1 receptor and mediated through CYP4A and ERK1/2 (Figures 4 and 5).…”
Section: Figurementioning
confidence: 91%
See 2 more Smart Citations
“…We tested the specificity and sensitivity of commercially available BK b1-subunit antibodies using tissues from WT and BK b1-KO mice, and found that under denaturing conditions these antibodies lacked either specificity or sensitivity for BK b1-subunit in BK b1-subunit enriched tissues from C57BL/6 mice. The antibodies evaluated in this study have been used previously in different tissues including blood vessels, tracheal smooth muscle cells, and kidney from rats, mice, and humans (Matharoo-Ball et al 2003;Chang et al 2006;Grimm et al 2007Grimm et al , 2009Yang et al 2009Yang et al , 2013Albarwani et al 2010;Xie et al 2010;Zhang et al 2010;Howitt et al 2011;Ahn et al 2012;Loot et al 2012;Lu et al 2012;Evseev et al 2013;Kunduri et al 2013;Shi et al 2013a,b;Zheng et al 2013;Evanson et al 2014;Leo et al 2014;Nystoriak et al 2014;Pabbidi et al 2014;Yi et al 2014). However, our study is the first to test the specificity and sensitivity of all commercially available antibodies for detection of the BK b1subunit using BK b1-subunit KO mice test.…”
Section: Discussionmentioning
confidence: 99%